A retrospective analysis and systematic review of the areas of entertainment computing and persuasive technologies for health - Silva, Paula Alexandra; Bermúdez i Badia, Sergi; Cameirão, Mónica S. (Frontiers in Computer Science, 2023)
The areas of entertainment computing and persuasive technologies are interdisciplinary fields that have gained increasing attention in the last decades. Health is one of the domains that has leveraged the benefits of fun to improve the results of its technology-enabled interventions. Previous work has reviewed the area of health entertainment from many different perspectives; however, an integrative analysis across disciplines (health sciences and computer science and engineering) throughout the development and validation cycle of technologies in this domain is missing. Having such an in-depth retrospective analysis would shed light on how research on entertainment computing and persuasive technologies for health has evolved, acknowledging its contributions, recognizing its strengths and limitations, and, as a result, allowing for the definition of ways forward. This paper engages in an unprecedented systematic review of the work produced between 2004-2017 in this area. From an initial total of 10350 retrieved results, a total of 1307 full texts were included in this review and were thoroughly examined to gain a retrospective understanding of the type of studies that have been produced. Among others, this systematic review reports on the trends, venues of publication, and the characteristics of the studies including methodologies, sample characteristics, study design, the type of solutions produced, the conditions and domains of application, and the purpose of the studies. Results show that there is a growing body of research in the area, with most studies being published in roughly the same venues, and where the lion’s share of solutions fall into the area of health rehabilitation and motor conditions. With regards to the most addressed health domains, our review shows that most solutions produced are aimed at stroke and fitness, followed by balance training. Most studies (82.3%) are conducted with their target population, mostly adults (18-49 yo), and are conducted either in the lab or in clinical settings. However, the median sample size of the studies has remained stable (N=20) in the last decades. Regarding technology, 2D and 3D solutions are equally used, and most systems employ movement sensors and are single-user. Finally, only 21.4% of the studies are performed using validated instruments.